Expression profile of microRNAs in bronchoalveolar lavage fluid of rats as predictors for smoke inhalation injury. Issue 8 (December 2018) - Xiao, Peixin; Sun, Shuli; Cao, Juan; Wang, Jing; Li, Helin; Hou, Shike; Ding, Hui; Liu, Ziquan; Fang, Yifei; Bai, Song; Qin, Xiaojing; Yu, Fei; et al.
Highlights: Long-term effects of smoke inhalation cause pulmonary fibrosis. Smoke inhalation caused a significantly increase of inflammatory response. Smoke inhalation injury results in changes of miRNAs in BALF. A subset of seven miRNAs may be used for diagnosis of smoke inhalation injury. Abstract: Smoke inhalation injury (SII) is an independent risk factor for morbidity and mortality in patients with severe burns, however, the underlying mechanisms of SII are still not fully understood. In our study, we established an advanced rat model of SII based on the previous work, and explored the dynamic changes of pathophysiology and inflammatory factors during 28 days post SII. We also measured the different expressions of miRNAs in bronchoalveolar lavage fluid (BALF) between SII and normal control rats by miRNA microarray. At 1 day after smoke inhalation, the histopathological results exhibited inflammatory exudates in the lung tissue with significant edema. As time went on, the lung injuries gradually appeared at alveolar septum thickening and alveolar collapse, which suggested that it further induced damage to lung parenchyma by smoke inhalation. Particularly, the collagen deposition indicating pulmonary fibrosis happened at 28 days post-injury. Plasma IL-6 and TNF-a were significantly increased after 1 day of smoke inhalation. Plasma IL-10, BALF TNF-α and IL-10 were significantly increased after 2 days of smoke inhalation. By extending the observation time, the levels of plasma IL-6, BALF TNF-a and IL-10 appeared a second peak again after 14 days of injury. Compared with the normal control group, there were 23 upregulated miRNAs and 2 downregulated miRNAs in BALF of SII group at 1 day post-injury. RT-qPCR validation assay confirmed that the changes of miR-34c-5p, miR-92b-3p, miR-205, miR-34b-3p, miR-92a-3p, let-7b-5p, let-7c-5p in BALF were consistent with the conclusion of the miRNA microarray. In summary, we showed the dynamic changes of pathologic changes and inflammatory factors in rats with SII, and a subset of seven miRNAs changed in BALF after SII which may be used for diagnosis and potential therapeutic targets.